Better big or strained? Deformations of shape persistent arylene butadiynylene macrocycles. (7th March 2023) - Małecki, Marcin S.; Dopieralski, Przemysław; Gulia, Nurbey; Pigulski, Bartłomiej; Lis, Tadeusz; Szafert, Sławomir
Abstract : A series of arylene butadiynylene macrocycles has been crystallographically characterized showing that the flexibility of these systems depends on the intracyclic steric hindrance. Abstract : Shape-persistent macrocycles have been of interest for many years to researchers due to their potential in synthesis and materials chemistry. They are regarded as reasonably rigid and in many cases they are able to spontaneously aggregate forming supramolecular assemblies. The dependence of a steric hindrance located on oxygen atoms in 2, 6-bis-acetylenephenolates on the structure of macrocycles obtained from these precursors by Eglinton homocoupling has been investigated. A small library of crystal structures of arylene butadiynylene species has been obtained and analyzed in detail. Our results showed that regardless of the steric hindrance usually a wide range of macrocycles is formed (starting from tetramers) even though the smaller derivatives are significantly deviated from planarity, which might result from avoiding too much strain in these macrocyclic, cross-conjugated molecules.